Two novel Oidiodendron species isolated from roots of Vaccinium boninense in the Bonin Islands, Japan - Hirose, Dai; Tokiwa, Toshiyuki; Yaguchi, Takashi (Phytotaxa, 2022)
Four strains of the fungal genus Oidiodendron were isolated from the fine roots of Vaccinium boniense which is distributed only on the Bonin Islands, Japan. Two new species, Oidiodendron tokumasui (NBRC 115411T) and Oidiodendron boninense (NBRC 115392T), are described in this paper. Molecular phylogenetic analyses based on multigene sequence-data showed that each novel species formed a unique clade. Oidiodendron tokumasui is phylogenetically related to O. maius but can be distinguished from O. maius by good growth at 25‒30 ˚C and pH 7‒9, colony diameter after 28 days, and length of the conidiophores. Oidiodendron boninense is phylogenetically related to O. setiferum, O. rammosum, O. muniellense, and O. fuscum but differs from those four species in the following aspects: good growth at 25 ˚C and pH 7, absence of melanized appendages, spinulate and thick-walled conidia, and length of the conidiophores. Both new species formed ericoid mycorrhizal-like hyphal coils in the rhizodermal cells of sterile blueberry seedlings in vitro.